Propagating Bright Knots in the Chromospheric Fibrils - Shaoxuan Tong; Jun Zhang; Tao Ding (The Astrophysical Journal)
The solar chromosphere is a crucial layer for resolving the problem of atmospheric heating. There are many bright features, which are considered as the thermal signals for heating the atmosphere, and these features are suggested to have resulted from either magnetic reconnection or wave dissipation. It has been reported that a large number of propagating bright knots are detected in the chromosphere and corona. In this paper, we employ the high-resolution chromospheric H α data from the New Vacuum Solar Telescope to study the propagating bright knots. As the propagating bright knots move along the chromospheric fibrils, we select isolated and clear fibrils and track the knots along these fibrils. While the number of knots in a fibril region is equal to or greater than 5, the fibril and the knots are recorded. Based on the data on 2019 September 4, we detected 98 knots, and these knots move along 13 fibrils. On 2019 November 2, 87 knots, which move along 12 fibrils, were recorded. These propagating bright knots have an average area of around 0.8 Mm ^2 , with propagating distances from 190 to 2450 km, propagating velocities from 5 to 51 km s ^−1 , and an average lifetime of 71 s. To examine the relationship between the knots and the photospheric magnetic fields, we measure the field underneath these knots. The average magnetic flux densities are less than 10 Gauss, comparable with the noise level. We suggest that these knots are not produced by magnetic reconnection, but rather by wave dissipation.